Factors Influencing Johannesburg - van de Sande, Panayoty (My University, 2011)
The inner city of Johannesburg has recently gone through a period of renewal; it was just a decade ago that Johannesburg was described as “The City of Filth” (City Press, 1997; Pg: 4), owing to increased crime, decreased confidence, and fleeing tenants and landlords, which led to the “decrease in inner city residential property prices and in many cases negative equity from which many landlords just walked away” (City Press, 1997; Pg: 7). Today “crime rates are down, occupancy rates are up, investment is increasing as confidence improves and cleanliness has returned” (Turner & Townsend, 2005; Pg: 1). The Johannesburg inner city rejuvenation has attracted investors, some of whom have been successful and others not. This research identified the many factors that affect Johannesburg’s inner city residential property values and grouped the identified factors into the categories: “High Level Factors”, “Low Level Factors” and “Individual Factors”. Participants were then identified from three distinct groups: “Successful Investors”, “Unsuccessful Investors” and “Service Providers” to those investors. Participants were asked to rate the significance of each factor and category. The research outcomes were as follows: Successful Investors and Service Providers to the investors had similar views and ranked the Individual Factors as being most significant, followed by Low Level Factors and then High Level Factors. These results indicated that Successful Investors took responsibility for their investments, and displayed an internal locus of control, which ensured that they succeeded. Unsuccessful Investors rated High Level Factors which were outside of their control and had an external locus of control as playing a significant role in the demise of their investments while the Low Level Factors and Individual Factors were seen as not having a significant impact on the value of inner city residential property values. What was evident from all participants was that at some time they had all felt that residential property within the inner city of Johannesburg was a good investment and that this investment would give them positive returns.
MBA - WBS
Keywords: Residential property values